ANALYSIS OF CONSTITUTIONAL AND LEGAL FOUNDATIONS OF THE RIGHT OF CITIZENS TO ACCESS THE INFORMATION ON THE ACTIVITIES OF PUBLIC AUTHORITIES IN THE UNITED STATES OF AMERICA - Murina Tazieva (Гуманитарные и юридические исследования)
Nowadays the legal opportunity for the public to receive information on the activities of public authorities is of great importance. Appropriate legislation exists in all democratic countries of the world. The initial provisions on the human and citizen's right to access information on the activities of public authorities are contained in the constitutions of the countries of the world, or acts of constitutional legislation. In the United States of America, as in the state with the oldest written constitutions, there are unique features of the legal regulation of citizens' access to information on the activities of the public administration. Despite the basic legal norm of the constitution on freedom of speech, it is necessary to consider the rights to get access to information in the US in close connection with the right to petition government authorities. This is confirmed by the analysis of the current constitutional legislation, the norms of which are aimed at establishing and guaranteeing, as well as creating the mechanism for exercising the right to access information on the activities of public authorities. The US population has many opportunities to demand and receive information from authorities. At the same time, as in other states, the US has a legally established a list of grounds on which applicants may be denied information.